2024
DOI: 10.3389/fphar.2023.1301561
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of knowledge, attitude, practice and predictors of self-medication with antibiotics among medical and non-medical students in Tanzania

Lusajo Shitindi,
Omary Issa,
Baraka P. Poyongo
et al.

Abstract: Introduction: Self-medication with antibiotics (SMA) is a widespread problem in developing nations, including Tanzania.Methods: This study compared knowledge, attitudes, practices, and factors influencing antibiotic SMA among medical and non-medical students.Results: The prevalence of SMA among medical students was 49.1% and 59.2% among non-medical students, respectively. The mean knowledge score of medical students (6.4) was significantly higher (p-value <0.001) than that of non-medical students (5.6).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
3
1
Order By: Relevance
“…SM with AMAs was found to be 28.7% in our study which is much lower than Nabi et al (68%) [16], and Nakato et al [17], (80-93%) and Wahab et al (61%) [18], and Shitindi et al [19].…”
Section: Discussioncontrasting
confidence: 67%
“…SM with AMAs was found to be 28.7% in our study which is much lower than Nabi et al (68%) [16], and Nakato et al [17], (80-93%) and Wahab et al (61%) [18], and Shitindi et al [19].…”
Section: Discussioncontrasting
confidence: 67%
“…Studies such as those by Alves et al 41 underscore the role of knowledge in promoting safe self-medication practices, preventing indiscriminate use . Shitindi et al 42 contend that a lack of proper knowledge about medicines is a strong predictor of self-medication practices. Conversely, research by Abebe et al 2 suggests that while university students may possess good knowledge about self-medication, negative attitudes towards it are associated with reduced practice.…”
Section: Introductionmentioning
confidence: 99%
“…A critical aspect identified in various studies is the knowledge about adverse drug reactions (ADR) and the attitudes towards them, which significantly influence self-medication 42 , 44 . Studies by Gedam and Kuchya 45 and Sivadasan et al 46 emphasize the importance of knowledge about ADR in shaping proper attitudes and responsible self-medication practices.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that people rarely or never check the expiry date of the OTC medications they took. This is concerning since failing to verify a medication's expiration date might result in an accumulation of expired pharmaceuticals in the home and numerous negative side effects [11].…”
Section: Introductionmentioning
confidence: 99%